2014
DOI: 10.1007/s13142-014-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Quitting the “Cancer Tube”: a qualitative examination of the process of indoor tanning cessation

Abstract: This study examined health belief model (HBM) relevant constructs in the context of indoor tanning cessation. Telephone interviews were conducted between December 2011 and April 2012 with participants drawn from the Growing Up Today Study (GUTS) population, specifically, former tanning bed users (N=14, all females; mean age, 25.65 years) who reported frequent use in 2007, but had quit by 2010. Participants identified important motivations for quitting including health and financial reasons and the central role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Indoor tanning activates the same reward centers in the brain associated with other addictive behaviors (Harrington et al, 2012). A study of females who used to tan but had, at least temporarily, stopped found that psychological factors more than physical factors made it difficult for them to continue abstaining (Banerjee et al, 2014). Therefore, message creators who hope to dissuade young women from using indoor tanning devices may benefit from examining the influence of affect and outcome expectations in other addictive behavior domains, particularly given the links between tanning and substance use among college women (Mosher and Danoff-Burg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indoor tanning activates the same reward centers in the brain associated with other addictive behaviors (Harrington et al, 2012). A study of females who used to tan but had, at least temporarily, stopped found that psychological factors more than physical factors made it difficult for them to continue abstaining (Banerjee et al, 2014). Therefore, message creators who hope to dissuade young women from using indoor tanning devices may benefit from examining the influence of affect and outcome expectations in other addictive behavior domains, particularly given the links between tanning and substance use among college women (Mosher and Danoff-Burg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More than 35 % of their subjects found quitting somewhat difficult and had a psychological urge to resume tanning. [1] Indeed, the latest research in Cell corroborates this subjective sense of addiction experienced by the patients; in a rodent model, researchers found an endorphin-mediated method of addiction to UV light. [2] Aside from psychological challenges, Banerjee et al also uncovered practical obstacles, such as social pressure and even re-enrollment promotions from salons.…”
mentioning
confidence: 87%
“…[2] Aside from psychological challenges, Banerjee et al also uncovered practical obstacles, such as social pressure and even re-enrollment promotions from salons. [1] With the challenges to cessation that the study uncovered, it is clear that the best method of decreasing exposure to indoor tanning would be to stop tanners before they start this toxic behavior.…”
mentioning
confidence: 99%
“…In turn, alternative approaches may be needed to intervene for these indoor tanners, who may differ from the broader population. 374…”
Section: Individualsmentioning
confidence: 99%